2014
DOI: 10.1016/j.brainres.2014.08.022
|View full text |Cite
|
Sign up to set email alerts
|

The protective role of prosaposin and its receptors in the nervous system

Abstract: Prosaposin (also known as SGP-1) is an intriguing multifunctional protein that plays roles both intracellularly, as a regulator of lysosomal enzyme function, and extracellularly, as a secreted factor with neuroprotective and glioprotective effects. Following secretion, prosaposin can undergo endocytosis via an interaction with the low-density lipoprotein-related receptor 1 (LRP1). The ability of secreted prosaposin to promote protective effects in the nervous system is known to involve activation of G proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
88
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(105 citation statements)
references
References 142 publications
6
88
0
2
Order By: Relevance
“…The natural ligand for GPR37L1 remains uncertain, and in the studies described here, we assessed two peptides that have been proposed as ligands for GPR37L1 and/or GPR37: prosaptide 25; 42; 43 and head activator (HA) 44; 45 However, no significant increases in receptor signaling activity were observed with either peptide, and therefore the previously-reported agonistic actions of these two peptides could not be confirmed here. It is possible that the regulation of GPR37/GPR37L1 signaling activity by these peptides is dependent on cellular context and/or other variables, although another recent study also reported a lack of activation of GPR37L1 signaling by prosaptide 46 .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The natural ligand for GPR37L1 remains uncertain, and in the studies described here, we assessed two peptides that have been proposed as ligands for GPR37L1 and/or GPR37: prosaptide 25; 42; 43 and head activator (HA) 44; 45 However, no significant increases in receptor signaling activity were observed with either peptide, and therefore the previously-reported agonistic actions of these two peptides could not be confirmed here. It is possible that the regulation of GPR37/GPR37L1 signaling activity by these peptides is dependent on cellular context and/or other variables, although another recent study also reported a lack of activation of GPR37L1 signaling by prosaptide 46 .…”
Section: Discussionmentioning
confidence: 93%
“…Previous reports have described prosaptide, a peptide fragment of prosaposin 25; 42; 43 , and the Hydra undecapeptide head activator (HA) 44; 45 as potential ligands of GPR37 and GPR37L1. To assess the signaling activity of GPR37L1 WT vs. the K349N mutant, induction of ERK phosphorylation was measured, as signaling from both GPR37 and GPR37L1 has been shown to stimulate ERK phosphorylation 25 .…”
Section: Resultsmentioning
confidence: 99%
“…5D) or co-culture of 4T1-MSC in a stiff tumor microenvironment induce the expression of PSAP in 4T1 cancer cells. It is worth noting that PSAP up-take via endocytosis in certain types of cells, including nerve cells and fibroblasts, was previously reported(12). …”
Section: Resultsmentioning
confidence: 67%
“…Prosaposin (PSAP, Psap) is the precursor protein for saposin A–D, which are lysosomal activator proteins that facilitate the hydrolysis of sphingolipids(12). In addition to the function in lysosome, PSAP is also secreted as full-length prosaposin that regulates neurotrophic action in the nerve system(12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation